Protective effect of crocin on electromagnetic field-induced testicular damage and heat shock protein A2 expression in male BALB/c mice - shayan Vafaei; Fatemeh Motejaded; Alireza Ebrahimzadeh-bideskan (Iranian Journal of Basic Medical Sciences, 2020)
Objective(s): Exposure to electromagnetic fields (EMF) emitted from mobile phones may cause a deleterious effect on human health and may affect the male reproductive system. Crocin, a carotenoid isolated from Crocus Sativus L. (Saffron), is a phar‌macologically active component of saffron. So, this study was conducted to investigate the protective effect of crocin on the male reproductive system of 60 day old mice after EMF exposure. Materials and Methods: Twenty-four male Balb/c mice were randomly divided into 4 groups: 1. Em group (2100 MHZ); 2. Cr group (50 mg/kg); 3. Em+Cr group (2100 MHZ+50 mg/kg), and 4. Control group. Sperm parameters (count, and abnormal percent), testis weight index, testis volume, seminiferous tubule diam‌eter, germinal epithelium thickness, LH, FSH and testosterone serum level, testicular Heat shock protein A2 (HspA2) immunoreactivity, and apoptosis were evaluated. Results: HspA2 immunoreactivity, apoptosis in the germinal epithelium and abnormal sperm were increased in Em group compared with the control group (P<0.05). Sperm count, LH, and testosterone serum level were decreased in the Em group compared with the control group (P<0.05). These parameters were improved in the Em+Cr group compared with Em group significantly (P<0.05). Conclusion: our findings revealed that EMF exposure leads to harmful impressions on the male reproductive system, while crocin can attenuate EMF-induced destructive effects.